Les situations d'urgence qui permettent en droit international de suspendre les droits de l'homme - Tremblay, Guy (Les Cahiers de droit, 1977)
This article describes and comments the types of emergency situations which are recognised by the international law of human rights as justifying suspension of specific rights and freedoms. The European standards on this matter are extensively analysed, and subsidiary consideration is given to many connected agreements and reports sponsored by international organisations. The introduction asks whether the public danger must always be "officially proclaimed". It then indicates what state organs should be competent to declare an emergency and to what extent their decisions in this respect are liable to effective judicial and political control. On the availability of such checks depends the enforcement of those further safeguards which international bills of rights have set with respect to when a crisis actually prevails. The first Chapter considers the terms whereby the derogation clauses of international charters of human rights refer to emergency situations and draws upon the construction which has been officially given to the relevant provisions. The definition of a public danger may be more or less encompassing and consequently more or less permissive. Thus, the reference in article 4(3)(c) of the European Convention on Human Rights to threats to the "well-being" in addition to threats to the "life" of the community has significantly broadened the scope of emergency exceptions to the freedom from forced or compulsory labour. Under the American Convention on Human Rights, derogatory measures can be taken when a situation "threatens the independence or security of a State Party", and it is demonstrated that this provides no valuable test as to whether a proclamation of emergency corresponds to an actual danger. The same is true of the expression "(threat to) the interests of the people" which appeared in the drafts of both the European Convention and the UN Covenant on Civil and Political Rights. These two agreements, as well as the European Social Charter, condone the taking of derogatory measures wherever the "life of the nation" is endangered, and the meaning of this phrase is studied in the light of the relevant preparatory works and the judicial pronouncements of the European Commission and Court of Human Rights. In the second Chapter, critical sets of circumstances involving revolutionary elements are considered with a view to ascertaining whether they meet the requirements of international bills or rights as regards the nature of the crisis. The main problem which was brought before the European Commission with respect to this matter is raised by the coming to power of an unconstitutional government. Has such a government the right to derogate from the Convention in order to preserve its own existence? An affirmative answer was given in the First Greek Case. Nevertheless, it is submitted that the Report of the Commission on this Case embodies a considerably hardened approach as compared to its earlier case-law. Moreover, on the merits of the Case, the Commission has not stuck to the right question and has overlooked the main element: it has, in fact, decided that on April 21, 1967, no public emergency threatened, the life of the constitutional, rather than the revolutionary, Government of Greece and it has not drawn at all upon the effects of the occurence of the coup itself. Threats to the territorial integrity of Contracting Parties are then shortly discussed and, with particular reference to self-determination, it is shown that most derogation clauses favour the preservation of the status quo. The same would hold good when it comes to threats to democracy as such, whether they be raised lawfully or not. In this connection, the European Commission appears to have qualified the sweeping language that it originally used in the German Communist Party Case. As to duration, finally. Chapter three asks whether the periods just preceding and just following a public danger are themselves covered by the relevant derogatory provisions. Anticipatory proclamations of emergency are invariably accepted as legitimate. All derogation clauses indicate that it is the threat which must be actual and not the hostilities, though these must be imminent. The European Commission has not applied consistently its own views on this matter. Conversely, transitional states of emergency may be acceptable from an economic standpoint, but not in the field of human rights. The difficulty here is to make sure that a crisis has not merely been placed under control and that a withdrawal of derogatory measures will not revive the threat to the life of the nation. This problem, it is submitted, must be treated in conjunction with the determination whether the suspension of rights and freedoms remained "strictly required by the exigencies of the situation". The article concludes that valuable standards have been set on the international plane as to conditions regulating the existence of those public emergencies which condone suspension of human rights. Most of these tend to make sure that the legal conception of a public danger continuously relates to an actual crisis and remains essentially limited in substance and in time. The case is also made for the retention of judicial control over the type of "political" decision involved.